Evaluasi Performa Furnace EDC (Ethyl Dichloride) Cracker di VCM (Vinyl Chloride Monomer)-1 Plant - Rohiman Ahmad Zulkipli; Rachmadi Rachmadi; Yafi Fadhlurohman Muhammad (Universitas Darul Ulum, 2025)
Furnaces in the production of VCM (Vinyl Chloride Monomer) must be operated with optimal efficiency to maximize production and minimize the formation of impurities (coke). Furnace efficiency is evaluated based on the ratio of heat generated from fuel combustion to heat absorbed by the EDC (Ethyl Dichloride) fluid, and is a key indicator of operational feasibility. In addition, the pressure difference of the inlet convection and outlet radiant sections is used as an additional parameter, where an increase in this value reflects the accumulation of deposits in the tubes. If the efficiency drops below the minimum operating conditions or the pressure difference between the convection inlet and outlet radiant section exceeds 4 kg/cm2G, the furnace is considered unfit for operation and decoking must be performed, which will increase operating costs. During the 12 days of monitoring (measurement every 8 hours), the average efficiency was 85.370%, the highest value was 87.348%, and the lowest value was 83.764%. The efficiency values tended to fluctuate and were below the minimum operating condition (88.898%). This is due to changes in operating conditions and manual control. Therefore, although the pressure difference is still below the threshold of 4 kg/cm2G, the furnace is considered unfit for operation.